TRADITIONAL GAME (GAPYAK) AS EFFORT TO DEVELOP COMMUNICATION AND STUDENT COOPERATION IN 1 BUMIREJO ELEMENTARY SCHOOL - Ingtiarti Ingtiarti; Nur Rofiqoh; Ivan Arifudin; Kartika Chrysti Suryandari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Recently, traditional game among students, particularly gapyak, have begun to fade and are forgotten due to the times. Gapyak has been replaced by modern technology-based games that have a high level of addiction, resulting in changes in student behavior and habits. They tend to be less socializing with people around. As a result, students lack of communication and collaboration in daily life. This research to foster communication and collaboration of students in SD Negeri 1 Bumirejo. The research subjects were 27 grade V students of SD Negeri 1 Bumirejo. The object of the research is communication and student collaboration in the game Gapyak. The research design is descriptive qualitative with data collection techniques through observation sheets and interview sheets which are then described. The results showed that the traditional game Gapyak in communicating "good" criteria with a percentage of 80%, and in cooperation the criteria "good" with a percentage of 83%. This can be seen from observations that show that students are able to communicate, cooperate, and responsible.